Improving Critical Thinking Skills through Discovery Learning: Case Study at SMP Negeri 2 Central Kupang - Djalo, Aloysius; Missa, Hildegradis; Ndukang, Sardina (BIOEDUKASI, 2024)
Critical thinking skills, especially in science subjects, are insufficient because teachers only provide direct knowledge to students without giving students the opportunity to actively participate in learning. The aim of this research is to determine the influence of the Discovery Learning model towards the critical thinking skills of grade VII students at SMP Negeri 2 Kupang Tengah. This type of quantitative research uses a quasi experimental method. The research results show that the score of critical thinking skills of the students in experimental classes with an average posttest score of 80.46 higher than the pretest which is 50.04. Meanwhile, in the control class, the average pretest score was 45.21 and the average posttest score was 67.14. The results of the anacova test using the one-way anacova statistical analysis technique (one way-anacova) with the help of SPSS Version 23 obtained a probability value (sig) of 0.000 <from the set significant value of 0.05. Thus the null hypothesis (H 0 ) which states that there is no influence of the Discovery Learning model on students' critical thinking skills is rejected and the alternative hypothesis (Ha) which states that there is an influence of the Discovery Learning model on students' critical thinking skills is accepted. The conclusion of this research is that the Discovery Learning model influences the critical thinking skills of grade VII students at UPTD SMP Negeri 2 Kupang.